2021
DOI: 10.3390/w13233426
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Groundwater Suitability for Irrigation and Drinking Purposes in an Agricultural Region of the North China Plain

Abstract: Groundwater is an irreplaceable resource for irrigation and drinking in the North China Plain, and the quality of groundwater is of great importance to human health and social development. In this study, using the information from 59 groups of groundwater samples, groundwater quality conditions for irrigation and drinking purposes in an agricultural region of the North China Plain were analyzed. The groundwater belongs to a Quaternary loose rock pore water aquifer. The depths of shallow groundwater wells are 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…Comparing this to the studies done in various regions around the world, it appears that the results are somewhat consistent with the findings in Algeria and Iraq where ground water availability and suitability for agriculture are generally good with some areas of lower suitability (Kadri et al, 2022;Al Maliki et al, 2020). However, the results in North China plain indicate challenges with groundwater quality with less than a third of the area suitable for irrigation (Guo et al, 2021).…”
Section: Groundwater Availability and Suitabilitysupporting
confidence: 86%
“…Comparing this to the studies done in various regions around the world, it appears that the results are somewhat consistent with the findings in Algeria and Iraq where ground water availability and suitability for agriculture are generally good with some areas of lower suitability (Kadri et al, 2022;Al Maliki et al, 2020). However, the results in North China plain indicate challenges with groundwater quality with less than a third of the area suitable for irrigation (Guo et al, 2021).…”
Section: Groundwater Availability and Suitabilitysupporting
confidence: 86%
“…The Permeability Index (PI) assesses water movement capability in soil based on Ca 2+ , Mg 2+ , Na + , and HCO3 − concentrations [45]. It is a criterion for evaluating water quality suitability for agricultural irrigation, indicating soil permeability and drainage capacity [46].…”
Section: Npi Values Npi Interpretationmentioning
confidence: 99%
“…Bai et al investigated groundwater chemistry in Yongqing County in the northern part of the HBP and reported that groundwater total hardness concentration in phreatic aquifers was up to 840 mg/L [25]. Guo et al surveyed groundwater quality in the Bazhou irrigation district of the HBP and found that the total hardness concentration was up to 1483 mg/L in shallow groundwater but less than 90 mg/L in deep groundwater [26]. However, knowledge of the distribution and origins of hardness-rich shallow and deep groundwaters in the whole HBP is still limited.…”
Section: Introductionmentioning
confidence: 99%